Adolescent Health Care Education: A Community Intervention - Cholifah Cholifah; Siti Aisyah Lutfiyah; Umi Khoirun Nisak (Universitas Muhammadiyah Sidoarjo, 2023)
This study addresses the imperative of imparting effective hygiene practices to adolescents to mitigate menstrual health issues and infectious diseases. Focused on the Ketegan Village area, our Youth Health Care Education program aimed to instill the significance of proper hand hygiene, particularly in the context of viral and bacterial infections, among children aged 6-10 and adolescents aged 11-14. Employing a community-based approach, the program integrated educational activities to encourage consistent hand washing with soap before and after daily tasks. The outcomes revealed a substantial increase in awareness and adherence to hand hygiene practices among the targeted age groups. By equipping adolescents with essential knowledge during formative years, this initiative bears implications for sustained hygiene habits, thereby reducing the susceptibility to health complications associated with inadequate hygiene practices. Highlights: Community-based approach: The program utilized a community-focused strategy to ensure effective education and behavior change. Age-specific targeting: The initiative catered to different age groups, emphasizing the importance of hygiene practices among children and adolescents. Sustained impact: The study showed increased awareness and adherence to hand hygiene, indicating potential long-term benefits for health outcomes. Keywords: Adolescents, Hygiene practices, Youth Health Care Education program, Hand washing, Infectious diseases